Experimental investigation for optimization of robot spot welding parameters on low carbon steel JSC 590RN. (2022) - Tyagi, Abhishek; Kumar, Gaurav; Kumar, Mukesh; Neha, Eram; Wahid, Mohd Atif
Abstract: In this present research, optimization of spot-welding process parameters was done on the low carbon steel grade (JSC 590RN) using Taguchi L18 methodology. The main process parameters of spot welding namely electrode diameter (d), electrode force (F), welding current (I) and weld time (t) are taken to determine the quality characteristics of the joint. Heat affected Zone (HAZ), Nugget diameter (N-D) and tensile strength were taken as a quality characteristic for the improvement. For experimental trials, Taguchi L18 was selected. The GRA technique was used to observe the level of importance of process factors on spot welding. ANOVA results show that amid all control factors, welding current (39.19%) is the highest participating followed by weld time (23.81%). In this experiment, the confirmation result shows that it is possible to increases the weld quality up to 12.0081%.